1994
DOI: 10.1097/00000658-199409000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in Zollinger-Ellison Syndrome Alters the Natural History of Gastrinoma

Abstract: For the patient with Zollinger-Ellison syndrome without metastatic disease, surgical exploration with attempted curative gastrinoma resection is recommended because it may alter the natural history of this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 180 publications
(110 citation statements)
references
References 19 publications
3
101
0
6
Order By: Relevance
“…At least one study (6) that retrospectively analyzed the effect of surgical exploration in patients with large pancreatic PETs with MEN1 concluded that surgery did not prevent the development of hepatic metastases and extend survival. However, a recent study (58) in patients with primarily sporadic gastrinomas provided evidence that early surgical resection of the primary tumor decreased the probability of developing hepatic metastases. A second possibility would be to consider treating patients with aggressively growing PETs with MEN1 with a long-acting somatostatin analog (octreotide, lanreotide).…”
Section: Discussionmentioning
confidence: 99%
“…At least one study (6) that retrospectively analyzed the effect of surgical exploration in patients with large pancreatic PETs with MEN1 concluded that surgery did not prevent the development of hepatic metastases and extend survival. However, a recent study (58) in patients with primarily sporadic gastrinomas provided evidence that early surgical resection of the primary tumor decreased the probability of developing hepatic metastases. A second possibility would be to consider treating patients with aggressively growing PETs with MEN1 with a long-acting somatostatin analog (octreotide, lanreotide).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, other authors suggest a surgical treatment for tumors O3 cm in size or when a biochemical diagnosis is unequivocal (92,93). Nevertheless, patients who are conservatively treated have a risk of LM of 23-29% compared with 3-5% of those patients who undergo radical surgery (94,95). The extension of surgery in these patients is also a matter of debate.…”
Section: Surgery Of Nets In Multiple Endocrine Neoplasia Type 1 Patientsmentioning
confidence: 99%
“…Fraker et al (33) reported that gastrinoma patients administered conservative treatment exhibited a higher risk of liver metastasis (23%) compared with those who received surgery (3%). In the present study, of the 17 cases, 11 patients underwent surgery and 6 patients received conservative therapy due to metastasis or patient choice.…”
Section: Discussionmentioning
confidence: 99%